Why do French winegrowers adopt soil organic carbon sequestration practices? Understanding motivations and barriers - Payen, Florian Thomas; Moran, Dominic; Cahurel, Jean-Yves; Aitkenhead, Matthew; Alexander, Peter; MacLeod, Michael (Frontiers in Sustainable Food Systems, 2023)
Soil carbon sequestration (SCS) practices on French agricultural land are part of the portfolio of actions available to policymakers in the field of climate change mitigation and are central to the success of the ‘4 per 1000’ initiative, launched by France in 2015. To date, there has been limited research considering their applicability to vineyards. A survey was circulated to 506 French winegrowers to identify the adoption rate of six SCS practices in the viticulture sector (applying organic amendments, using biochar, returning pruning residues to the soil, no-tillage, cover cropping, and introducing or preserving hedges in the vineyard) and to explore motives and barriers to adoption. The survey also investigated ways of overcoming barriers to adoption and winegrowers’ perception of agri-environment measures. Differences in motivations and barriers between SCS practices were found, and winegrowers themselves suggested a need for improved communication of evidence about SCS practices and better-targeted policy incentives to support adoption.